The Principles of Ethics : In Two Volumes - Spencer, Herbert, 1820-1903 (Book collections on Project MUSE., 1978)
Though almost forgotten today, Herbert Spencer ranks as one of the foremost individualist philosophers. His influence in the latter half of the nineteenth century was immense. Spencer's name is usually linked with Darwin's, for it was he who penned the phrase, "survival of the fittest." Today in America he is most often admired for his trenchant essays in The Man Versus the State. But Spencer himself considered The Principles of Ethics to be his finest work. In the second volume, under "Justice," is his final statement on the role of the state. His formula for justice is summed up in these words: "Every man is free to do that which he wills, provided he infringes not the equal freedom of any other man."